Business Development Strategy for Increasing Sales in Food Businesses in Jombang Regency - Mansur, Muhammad; Supriyanto, Antok; Wibowo, Januar (GREENOMIKA, 2025)
Meatball business in Jombang Regency has significant growth potential due to its popularity among both residents and visitors. This research aims to explore and evaluate effective strategies for enhancing meatball enterprises in the area. Employing a mixed-method approach, the study integrates qualitative and quantitative data obtained through surveys, interviews, and market analysis. The findings reveal that key success factors for meatball businesses in Jombang include product quality, unique selling propositions, customer service, and marketing strategies. The study emphasizes the need for product innovation, the utilization of digital marketing, and strategic collaborations with local suppliers and distributors. Furthermore, it highlights the importance of government support in offering training and financial aid to small and medium-sized enterprises (SMEs). Recommendations for meatball business owners involve improving product differentiation, using social media to expand reach, and participating in local food events to boost brand recognition. This research provides valuable insights into SME development in the food industry and offers practical strategies for entrepreneurs aiming to succeed in Jombang Regency's competitive market.